Analisis Faktor yang Mempengaruhi Keterampilan Berbicara Selama Proses Pembelajaran Mahasiswa Semester 2 Program Studi BK FIP Universitas PGRI Semarang - Hanifa, Azza Dhifa Zayyan (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2023)
The low speaking skills possessed by students such as, insecurity and nervousness when dealing with many people, this makes students stammer so that they often say the word